The Effect Of Company Size And Capital Structure On Firm Value With Profitability As An Intervening Variable - Rosy Meidiana Puri; Yuliani Yuliani; Kemas M. Husni Thamrin (Green Publisher Indonesia, 2024)
This study investigates the influence of company size and capital structure on firm value with profitability as an intervening variable in the Property and Real Estate sector companies listed on the Indonesia Stock Exchange during the period 2016-2022. Using a sample of 20 companies, this research employs a quantitative method with path analysis using the Eviews program. The results indicate that company size does not have a significant influence on profitability, while capital structure has a positive and significant impact on profitability. Company size positively and significantly affects firm value, whereas capital structure does not significantly influence firm value. Profitability shows a positive and significant effect on firm value and acts as an intervening variable between company size and firm value, as well as between capital structure and firm value. The theoretical implications of this research underline aspects of agency theory and the relationship among company size, profitability, and firm value. Practically, the findings suggest that profitability is more crucial than company size in determining firm value. It also emphasizes the need to optimize capital structure to prevent negative impacts on firm value.